Dos gramíneas exóticas con potencial invasor nuevas en la provincia de Huelva - Sánchez Gullón, Enrique; Muñoz Rodríguez, Adolfo F. (Acta Botanica Malacitana, 2018)
Se citan dos gramíneas exóticas con potencial invasor nuevas en la provincia de Huelva